Spatio-temporal characteristics of urban heat Island of Jakarta metropolitan - Siswanto Siswanto; Danang Eko Nuryanto; Muhammad Rezza Ferdiansyah; Agita Devi Prastiwi; Ova Candra Dewi; Ahmad Gamal; Muhammad Dimyati (Remote Sensing Applications: Society and Environment, 2023)

Seasonal sea breeze variation analysis based on multi‐year near‐surface observations in Jakarta, Indonesia - I Dewa Gede Agung Junnaedhi; Atsushi Inagaki; Muhammad Rezza Ferdiansyah; Manabu Kanda (International Journal of Climatology, 2023)
In this study, multi‐year near‐surface observations were conducted at two sites in Jakarta, Indonesia to analyse seasonal sea breeze variation. Seasonal length was defined using observed zonal wind components, the rainy season was defined as December–March, and the dry season was defined as May–September. We found that the sea breeze in Jakarta started earlier, propagated more rapidly, and lasted for a shorter period of time during the rainy than dry season. Variation in the air temperature difference between urban and coastal areas of Jakarta was the major factor driving sea breeze seasonal variation. During the rainy season, night‐time cloud downwelling decreased this air temperature difference, causing earlier sea breeze onset and more rapid sea breeze propagation due to a weaker land breeze. By contrast, during the dry season, intense night‐time radiative cooling inland caused a strong negative temperature difference that produced a stronger land breeze, thus, slowing sea breeze propagation. Seasonal differences in urban surface heating and urban heat island circulation may also affect sea breeze onset and propagation speed. Discrepancies in thermal properties between urban core and coastal areas of Jakarta also prolonged positive temperature differences after sunset, thus extending the sea breeze duration in the dry season.